A Review on the Syntheses and Applications of the 5H-chromeno[2,3- b]pyridines - Ramazani, Ali; Kiani, Mohammad T.; Rezayati, Sobhan (Letters in Organic Chemistry, 2023)
5H-Chromeno[2,3-b]pyridine derivatives are a series of the most important compounds of chromenes with industrial, biological, and medicinal properties. These compounds are known as the privileged medicinal scaffold and can be synthesized by different methods such as multicomponent reactions (MCRs), Multicomponent coupling reactions (MCCRs), pot, atom, and step economy (PASE). In this review article, we have focused on the significant reactions for the syntheses and applications of 5H-chromeno[2,3-b] pyridines, including two-component reactions, three-component reactions, fourcomponent reactions, and multi-step reactions. This review is expected to serve as a useful conceptual overview and inspire the next generation to develop the different strategies for the preparation of 5HChromeno[ 2,3-b] pyridine derivatives.
Keywords: antibacterial